UJI ADAPTASI VARIETAS UNGGUL PADI DILAHAN SAWAH IRIGASI , DI KOTA JAYAPURA, PAPUA - Rohimah Handayani Sri Lestari; Fransiskus Palobo; Petrus Alexander Beding; Batseba M.W. Tiro (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2021)
Adaptation Test of High Yielding Rice Variety Seeds in Irrigated Rice Lands in Jayapura City, Papua. One of the factors influencing the increase in rice production is the use of location-specific new high yielding varieties (HYV) seeds. Farmers in Papua still often use rice seeds repeatedly without paying attention to the purity of the seeds, which can cause low productivity of rice in Papua, namely 4.35 t/ha when compared to national productivity of 5.11 t/ha. The research was conducted from April to August 2019 in district Muara Tami, Jayapura City. The treatments were arranged in Randomized Block Design (RBD) with one factor consisted of 5 varieties. The varietas used were high yielding varietas (Inpari 34, Inpari 43, Inpara 8, Inpago 8) and Mekongga variety as a comparison. All treatments were repeated 4 times. The result showed that the HYV productivity was influenced by yield components such as number of productive tillers, panicle lenght, 1000 grain weight and percentage of filled grain. The Inpari 34 and Inpago 8 varieties are more recommended to farmers due to a higher productivity compared to Inpari 43, Inpara 8 and Mekongga varieties by 7.74 t/ha and 7.22 t/ha respectively or an increase of 91.63% and 78.75% above the existing production (4.04 t/ha). Keywords: rice, adaptation, new high yielding varieties, productivity, irrigated land ABSTRAK Salah satu faktor yang mempengaruhi peningkatan produksi padi adalah penggunaan benih varietas unggul baru (VUB) spesifik lokasi. Petani Papua masih sering menggunakan benih padi berulang kali tanpa memperhatikan kemurnian benih sehingga dapat menyebabkan rendahnya produktivitas padi hanya 4,35 t/ha atau lebih rendah dibandingkan produktivitas nasional (5,11 t/ha). Tujuan penelitian adalah memperoleh benih VUB padi yang adaptif di lahan sawah beririgasi berdasarkan keragaan tananaman dan produktivitas. Penelitian dilakukan pada bulan April-Agustus 2019 di Koya Barat Distrik Muara Tami, Kota Jayapura. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK) faktor tunggal dengan varietas sebagai perlakuan. Varietas padi yang digunakan yaitu Inpari 34, Inpari 43, Inpara 8, Inpago 8, dan Mekongga varietas yang digunakan sebagai pembanding. Semua perlakuan diulang sebanyak 4 kali. Hasil penelitian menunjukkan bahwa produktivitas VUB padi dipengaruhi oleh komponen hasil seperti jumlah anakan produktif, panjang malai, berat 1000 gabah, dan persentase gabah isi. Varietas padi Inpari 34 dan Inpago 8 direkomendasikan untuk digunakan oleh petani karena produktivitasnya lebih tinggi, dibandingkan varietas Inpari 43, Inpara 8 dan Mekongga yaitu 7,74 t/ha dan 7,22 t/ha atau meningkat 91,63% dan 78,75% dibandingkan produksi eksisting (4,04 t/ha).Kata kunci: padi, adaptasi, varietas unggul baru, produktivitas, lahan sawah